Cost recovery rate analysis of inpatient services with national health insurance at cardiology poly in Hospital X - Diska Arliena Hafni; Eka Widyaningsih (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the cost recovery rate based on the type of case and service characteristics of inpatient national health insurance patients in cardiology poly and to find out the strategies used by the hospital if there is a financial loss. This research is quantitative descriptive research with a case study approach. Quantitative methods were used to compare hospital costs with the Indonesian case-based group tariff. This research data is in the form of primary data and secondary data. The object of research is the cost recovery rate of inpatients with national health insurance for cardiology poly in the period January-December 2023. This study obtained the results (1) overall for 19 types of cases, the cost recovery rate was 95%. (2) Based on patient service characteristics, the cost recovery rate of severity has an average value of 99%, the class of care has an average value of 96%, and the length of stay level has an average of 95%. (3) Hospital X's strategy is to increase the number of high social security organizing agency claims, evaluate hospital tariff components, and implement clinical pathways. The results of this study are expected to be input, consideration, and evaluation in controlling the cost of hospital services, so that there are not many losses. The limitation in this study is that the research was only conducted at the cardiology poly, so the sample studied was still small.